2009
DOI: 10.1007/s10528-009-9282-y
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Local Sheep Breeds in East Asia, Focusing on the Bayanbulak Sheep in China and the Sipsu Sheep in Bhutan

Abstract: The phylogenetic positions of the Bayanbulak sheep in China and the Sipsu sheep in Bhutan in the northern Asian sheep group were determined on the basis of allele frequency data for five informative and polymorphic loci of blood protein and nonproteins, such as transferrin (TF), arylesterase (ES), hemoglobin-beta (HB-beta), X-protein (XP), and potassium transport (KE), using different electrophoretic and ion-densitometric techniques. Based on Nei's genetic distance, clustering analysis by the UPGMA method show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Braman et al (1980) investigated haemoglobin polymorphism in a population of adult Cutthroat trout (Salmo clarkii) by employing starch gel electrophoresis and reported 12 haemoglobin components in the species. Haemoglobin polymorphism has been reported in cattle by Pal and Mummed (2014), in sheep Tsunoda et al (2010) and Al-Samarrae et al (2010), in goat Elmaci (2001) and in poultry (Dimri, 1978). Onyia et al (2015) documented the blood group and genotype of Clarias gariepinus and C. anguillaris.…”
Section: Introductionmentioning
confidence: 95%
“…Braman et al (1980) investigated haemoglobin polymorphism in a population of adult Cutthroat trout (Salmo clarkii) by employing starch gel electrophoresis and reported 12 haemoglobin components in the species. Haemoglobin polymorphism has been reported in cattle by Pal and Mummed (2014), in sheep Tsunoda et al (2010) and Al-Samarrae et al (2010), in goat Elmaci (2001) and in poultry (Dimri, 1978). Onyia et al (2015) documented the blood group and genotype of Clarias gariepinus and C. anguillaris.…”
Section: Introductionmentioning
confidence: 95%
“…Analysis of blood protein polymorphism showed that Jakar and Sakten are close and differ from the Sibsoo type. Jakar and Sakten are similar to Mongolian Chinese Sheep, Bhyanglung, and Baruwal, while Sipsoo shows similarity to Baruwal [51].…”
Section: Sheep (Ovis Aries)mentioning
confidence: 93%
“…Up to date study and research works on genetic diversity are conducted, and several marker genes associated with economically important traits have been studied, including the genetic structure of many livestock breeds. There have been studies on horses (Equus caballus) [69][70][71], cattle (Bos indicus) [19,20], indigenous chickens (Gallus domesticus) [60][61][62]65], sheep (Ovis aries) [50,51], and Mithun (Bos frontalis) [30][31][32]78,79], and research in molecular genetics can be a main tool in animal genetics, breeding, and conservation efforts in Bhutan. In the future, it is expected to see more in-depth studies in molecular genetics as a tool for conservation and sustainable utilization of farm animal genetic resources in Bhutan.…”
Section: A Novel Program To Facilitate Genetic Resources In Bhutanmentioning
confidence: 99%
“…Consequently, a lot of studies had been carried out in the area of morphological characterization (Salako and Ngere, 2002;Yakubu and Akinyemi, 2010;Yakubu and Ibrahim, 2011). Unfortunately, the morphological characteristics do not correspond to the genetic characteristics of blood protein and non-protein polymorphisms because the traits are complex in their mode of transmission and are influenced by the environment (Tsunoda et al, 2010). Blood protein characterization therefore may present higher accuracy procedures for a better measurement of genetic variation in sheep breeds because of their polymorphisms and simple mode of inheritance.…”
Section: Introductionmentioning
confidence: 99%